Bioetanol from Nipa Fibrous Waste (Nypa fruticans) Using Variation of Enzimatic Hydrolysis Method - Reni Yuliandani; Sofia Anita (Sistem Informasi, 2022)
Nipa waste from the nira harvest is a fibrous waste that no further processed by the people of Sabak Auh Village, Siak. Even though it has the potential to use as spent-resources product. It has high economic value. The nipa waste content was lignin which can be processed to produce second generation of bioethanol. It is an alternative material to substitute or mixture of petroleum. Bioethanol made in several stages, sample preparation, pretreatment, hydrolysis, fermentation and purification using distillation process. The purpose of this study was to compare the enzymatic hydrolysis process and acid in producing high-purity bioethanol. Hydrolysis process using white rot fungus extract as an enzyme and 1.5 N HCl solution (acid) as a hydrolyzing agent. The fermentation stage was used Saccharomyces cerevisiae yeast to convert glucose into bioethanol. Based on the results of the research, the hydrolysis process using enzymes was better of hydrolysis in producing bioethanol rather than acid. The highest purity was 11.78%, while bioethanol produced from the acid hydrolysis process had a purity level of 3.4%.